SOCIOCULTURAL APPROACH TO EXTREMISM - D. Guskov (Publishing House of the State University of Management, 2016)
In the article the author analyzes peculiarities of social and cultural approach to the phenomenon of extremism from the standpoint of its interaction with socio-cultural environment. Discloses a number of paradigms that characterize the socio-cultural approach in the framework of the scientific problem. In addition, the author describes several types of relationships norms and extremism with the positions of the sociocultural approach.